Alat Ukur Resiliensi Di Masa Pandemi Covid-19 Dalam Bentuk Brimop Untuk Siswa SMA - Nabila, Hafizatul; Muwakhidah, Muwakhidah (Universitas Nusantara PGRI Kediri, 2022)
The research aims to develop a resilience instrument in the form of a mobile brimop that has an adequate level of validity and is theoretically acceptable. This research model uses Brog and Gall, (1983). This development research uses data collection instruments, namely acceptability questionnaires for testing media experts, content experts and potential users. The data analysis technique used an inter-rater agreement model and descriptive statistical test. The results of the study have an index value of 1 in the media expert test, the content expert test index value of 0.97 prospective users of the Guidance and Counseling Teacher, the index value of 1 and the prospective users of the students, the results of the average percentage of 94.18% mean that the resilience instrument in the form of Brimop can accepted in theory.